2015
DOI: 10.15171/joddd.2015.013
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Oral and Intranasal Midazolam/Ketamine Sedation in 3‒6-year-old Uncooperative Dental Patients

Abstract: Background and aims. There are several known sedative drugs, with midazolam and ketamine being the most commonly used drugs in children. The aim of this study was to compare the effect of intranasal and oral midazolam plus ketamine in children with high levels of dental anxiety.Materials and methods.A crossover double-blind clinical trial was conducted on 23 uncooperative children aged 3-6 (negative or definitely negative by Frankel scale), who required at least two similar dental treatment visits. Cases were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 18 publications
1
34
2
Order By: Relevance
“…Seven studies (264 participants) were included (Fig 1 and S2 Text) [14,[21][22][23][24][25][26]. Excessive heterogeneity in outcome measures, study design, comparators, dosing, and indications for sedation precluded meta-analysis for any of the studies.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Seven studies (264 participants) were included (Fig 1 and S2 Text) [14,[21][22][23][24][25][26]. Excessive heterogeneity in outcome measures, study design, comparators, dosing, and indications for sedation precluded meta-analysis for any of the studies.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of included studies can be found in Table 1 and included children undergoing dental procedures (n = 5) [21,22,[24][25][26], laceration repair (n = 1) [14], and gastric aspiration (n = 1) [23]. No quasi-randomized trials were eligible.…”
Section: Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations